SIMULTANEOUS MULTI-SITE PHOTOMETRY OF LEO SATELLITES TO CHARACTERISE THEIR ROTATION STATES - Koshkin, N.; Shakun, L.; Melikyants, S.; Korobeynikova, E.; Strakhova, S.; Bilinskyi, A.; Vovchyk, Ye.; Kudak, V.; Motrunich, I.; Neubauer, I.; Kozhukhov, O.; Romanyuk, Ya.; et al. (Одеські астрономічні публікації, 2020)
The photometry of space objects (SO) makes it possible to determine their state of rotation around the center of mass, orientation of the rotation axis and rotation speed in the most cost-effective manner. However, the methods for determining the attitude parameters from photometric data from a single observation site (OS) require long series of high-quality and high-frequency measurements. We propose a method for determining the orientation parameters of slowly rotating SO based on simultaneous multi-site photometry with a high temporal resolution. Preconditions for planning and building a local photometric network that can accomplish such a task have been tested via computer simulation. Synchronous observations of the unoperated spacecraft TOPEX/Poseidon were carried out. They were attended by the observatories of Odessa, Lvov and Uzhgorod universities, as well as the observation station of the State Space Agency of Ukraine in Zalistsi, Khmelnytsky region, took part. Synchronous network-based photometric observations from three OSs enable us to calculate time lags between correlated light- curve segments and promptly determine the direction of rotation, as well as the spatial orientation of a SO’s spin axis and its angular spin rate. A local network of several distributed observation sites for synchronous monitoring of the rotation of various SO in LEO will make it possible to determine the rotation parameters of also slowly rotating objects that do not exhibit glints within their light curves.